Target Populations to Reduce Cesarean Rates After Induced Labor: A National Population-based Cohort Study. Issue 1 (24th March 2021) - Blanc-Petitjean, P.; Schmitz, T.; Salomé, M.; Goffinet, F.; Le Ray, C.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:406–412) There is a wide variation in the rate of cesarean delivery following induction of labor (IOL), and the reasons for this difference are unclear. The disparity may be explained in part by differences in obstetric practices or by risk factors like obesity, nulliparity, or previous cesarean delivery. This study used a 10-group classification system to identify populations with higher rates of cesarean delivery after IOL.